Odpowiedzi

2010-02-01T13:44:26+01:00
4(x-1)=-2(x+1)

4x-4=-2x-2
4x+2x=2
6x=2
x=1/3
spr;
4(1/3-1)=-2(1/3+1)
4/3-4=-2/3-2
-2i2/3=-2i2/3

3(2x+3)=x-1
6x+9=x-1
6x-x=-10
5x=-10
x=-2
spr:
3(2*(-2)+3)=-2-1
3(-4+3)=-3
3(-1)=-3
-3=-3

½-x=-½x
-x+1/2x=-1/2
-1/2x=-1/2
x=1
spr:
1/2-1=-1/2(1)
-1/2=-1/2
Najlepsza Odpowiedź!
2010-02-01T13:45:10+01:00
4(x-1)=-2(x+1)
4x-4=-2x-2
4x+2x=4-2
6x=2
x=2:6
x=⅓

spr.4(⅓-1)=-2(⅓+1)
4×(-⅔)=-2×⁴/₃
-2⅔=-2⅔


3(2x+3)=x-1
6x+9=x-1
6x-x=-1-9
5x=-10
x=-10:5
x=-2

spr.3[2×(-2)+3]=(-2)-1
3×-1=-3
-3=-3

½-x=-½x
-x+½x=-½
-½x=-½
x=1

spr.½-1=-½×1
-½=-½
2010-02-01T13:49:19+01:00
4(x-1)=-2(x+1)
4 x x - 4 x -1 = -2 x x + -2 x 1
4x - (-4) = 2x + -2
4x + 4 = 2x + -2
2x + 4 = -2
2x = 4 - (-2)
2x = 6
x = 6 : 2
x = 3

3(2x + 3) = x - 1
3 x 2x + 3 x 3 = x - 1
6x + 9 = x - 1
5x + 9 = - 1
5x = 9 - (-1)
5x = 10
x = 10 : 5
x = 2

1/2 - x = -1/2x
1/2 - x = -1/2 x x
-x = - x